(untitled) (Pesquisa Odontológica Brasileira, 2002)
The purpose of this study was to evaluate the presence of external resorption in non-vital teeth submitted to bleaching. The evaluated patients had at least one non-vital tooth, which had been bleached between 1986 and 1996. All teeth were submitted to bleaching with hydrogen peroxide and sodium perborate, as described by Busato et al.5,6. From 193 patients recalled for clinical and radiographic evaluation of bleached teeth, only 43 attended (54 teeth). The average time elapsed after bleaching was 3.5 years. The results revealed that none of the examined teeth had any degree of external cervical resorption.